Impact of Climate Change on Rainfall Trend in Johor, Malaysia - HANANI NAQIBAH BINTI MOHD AZMAN; SITI NAZAHIYAH BINTI RAHMAT (Recent Trends in Civil Engineering and Built Environment, 2023)
Climate change has a significant impact on shifting rainfall patterns in humid tropics; as a result, rainfall pattern changes are more noticeable in tropical regions like Malaysia. This study is carried out to forecast rainfall data for selected stations in Johor by using Statistical Downscaling Model (SDSM) and assess the trend of historical and future rainfall using a non-parametric test of Mann-Kendall Trend Test. The current study will concentrate on the implementation of a computational framework for downscaling climate data of two rainfall stations in Johor. The data gathered is focused on the historical rainfall data (1988-2017) and projected future rainfall data for the next 30 years, spanning the years 2008 to 2037 and 2038 to 2067. The data were processed and analyzed annually for 30 years period of different time series using the non-parametric Mann-Kendall Trend Test method. The first rainfall station, Stor JPS Johor Bahru, shows a significant increasing trend for the historical data (1988-2017) and projected future data (2008-2037) and (2038-2067). For the second rainfall station, Ldg. Lim Lim Bhd., Masai, the historical data (1988-2017) has no significant trend as the p-value is bigger than the significant level alpha equal to 0.05. However, both time series for projected future rainfall data present a significant increasing trend. The overall image of country rainfall distribution has become vital for future water resource planning and management. This study can generate a thorough assessment of future rainfall patterns, which is currently quite limited, particularly in Johor, Malaysia. The predicted rainfall data for Johor can be a way to prepare and strategize the upcoming season so that the society did not affect by the changing of the rainfall season due to climate change.